MODEL MANAJEMEN PEMBIAYAAN SEKOLAH ISLAM TERPADU BUSTANUL ULUM TERBANGGI BESAR LAMPUNG TENGAH - Rahmanto, Sujari (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2019)
Middle School Bustanul Ulum Terbanggi Besar, Central Lampung. The data collection techniques of this study were through observation, interviews, and documentation. Data analysis in this qualitative research starts from data reduction, data display, and verification or conclusion. Based on the results of the study it can be concluded that: 1) In financial planning (budgeting) education, all Islamic Schools TK, SD, SMP Bustanul Ulum Terbanggi Besar, Central Lampung are well in accordance with the Standards. 2) In the implementation (accounting) in accordance with applicable regulations. 3) at the stage of assessment (Auditing), all activities in the school there are examinations and supervision both kindergarten, elementary and junior high school 4) Integrated Islamic school financing management model that includes planning (budgeting), implementation (accounting) and evaluation of accounting and accountability systems.